Comparing the effects of nocturnal sleep and daytime napping on declarative memory consolidation - Lo, June C.; Dijk, Derk Jan; Groeger, John A. (PLoS ONE, 2014)
Nocturnal sleep and daytime napping facilitate memory consolidation for semantically related and unrelated word pairs. We contrasted forgetting of both kinds of materials across a 12-hour interval involving either nocturnal sleep or daytime wakefulness (experiment 1) and a 2-hour interval involving either daytime napping or wakefulness (experiment 2). Beneficial effects of post-learning nocturnal sleep and daytime napping were greater for unrelated word pairs (Cohen’s d = 0.71 and 0.68) than for related ones (Cohen’s d = 0.58 and 0.15). While the size of nocturnal sleep and daytime napping effects was similar for unrelated word pairs, for related pairs, the effect of nocturnal sleep was more prominent. Together, these findings suggest that sleep preferentially facilitates offline memory processing of materials that are more susceptible to forgetting.
Keywords: Memory consolidation; Sleep; Napping; Cognition